(untitled) (Ictus, 2022)
The functional neuroanatomy of language processing has not been fully elucidated. The known anatomical basis of speech have been proposed by various researchers, who have integrated different models of the brain regions involved. In this work, we address: historical aspects of the study of language (from Paul Broca until Hickok and Poeppel); some of the regions of the cerebral cortex that participate in the processing of speech, connected through the white matter; the proposed language models (Charcot, Grasset, Wernicke, Geschwind and dual model for auditory language processing); generalities of aphasias (causes and types); post-stroke aphasia and its treatment; and impact of neuronal plasticity in the treatment of aphasia.